ANALISIS VARIASI TEKANAN GAS O₂ TERHADAP WAKTU DAN BIAYA PADA PROSES PEMBUATAN COVER RADIATOR MOTOR DENGAN BAHAN PLAT BAJA MENGGUNAKAN MESIN FIBER LASER CUTTING - Vany Ramadhany; M.Fauzi Soulton; Zakiyah Amalia; Talifatim Machfuroh; Fica Aida Nadhifatul Aini; Siti Duratun Nasiqiati Rosady; Eli Novita Sari (Politeknik Negeri Banyuwangi, 2023)
In the industrial world, especially in the manufacturing industry, there are many technological developments that support better work processes. One of them is cutting technology or cutting machine, which has developed a lot of technology. There are more and more motorbike modifications for the use of transportation on the road or to be contested in motorbike modification competitions. One of them is the modification of the radiator cover which is most often found on motorcycles. Modification of the radiator cover using steel plate material has the advantage that it is stronger than the factory default radiator cover. This research uses an experimental method by varying the pressure of O2 gas then observing, recording and calculating research data. The purpose of this study was to determine the effect of variations in O2 gas pressure on the most optimal production time and estimate the production cost of the radiator cover for the motorcycle. From the results of observations and calculations of time and costs carried out in the radiator cover production process, it is obtained that the production time is 6.32 minutes / product and the production cost is Rp. 95.000,-/product. Keywords: Cover Radiator, production time, production costs.